Haemostatic variables during normal menstrual cycle - Knol, H. Marieke; Kemperman, Ramses F. J.; Kluin-Nelemans, Hanneke C.; Mulder, André B.; Meijer, Karina (Thrombosis and Haemostasis, 2012)
For a number of haemostatic factors menstrual cycle variation has been studied. Such variation could have clinical implications for the timing of haemostatic testing in women. It was our objective to systematically review the literature about evidence for timing of haemostatic testing during menstrual cycle.We searched MEDLINE, EMBASE and the Cochrane library to identify studies that measured haemostatic variables [platelet function, von Willebrand factor (VWF), factor VIII (FVIII), factor IX (FIX), factor XI (FXI), factor XIII (FXIII), D-dimer, plasminogen activator inhibitor-I (PAI-I), tissue plasminogen activator (tPA), urokinase-type plasminogen activator (uPA), α2-antiplasmin and fibrinogen] during normal menstrual cycle without hormonal contraceptives. Two investigators independently selected studies, and abstracted data in duplicate. We identified 1,046 studies of which we included 30 studies (25 longitudinal and 5 cross-sectional studies). All studies reported on haemostatic variables during menstrual cycle. Overall, most of the studies found no cyclic variation in VWF, FVIII, FXI, FXIII, fibrinolytic factors (PAI, t-PA, uPA, D-dimer and α2-antiplasmin) and fibrinogen. However, in studies where these variables showed any variation, they reached the lowest levels during menstrual and early follicular phase, especially for VWF, FVIII and platelet function tests. In conclusion, the optimal timing for haemostatic testing during menstrual cycle seems to be menstrual and early follicular phase.
Keywords: Menstrual cycle; haemostasis; von Willebrand factor; haemostatic variables